Imagined Extremist Communities: the Paradox of the Community-Driven Lone-Actor Terrorist - Sandboe, Inger Storm (Perspectives on terrorism, 2023)
This article introduces the concept of "imagined extremist communities," a term that encapsulates the unique social landscape where right-wing lone actors, despite not being affiliated with organised groups, partake in a form of communal interaction. By examining the cases of Anders Behring Breivik, Brenton Harrison Tarrant, and Philip Manshaus, this article illuminates how group-based and lone actors are more alike than what is conventionally expressed in existing research. Although lone actors are not subject to an external command like group-based actors are, the imagined extremist community functions as a "group" for lone actors and is, for all practical purposes, a corresponding alternative to a terror cell. During the radicalisation process, these individuals seek and turn to the imagined extremist community, enabling them to form a sense of belonging and identification and underscoring that these actors, although conventionally labelled as "lone," are immersed in an alternative culture that nurtures their ideas and sustains their extremist ideology. This becomes particularly evident through their cognitive radicalisation, a process amplified by their psychological predispositions. The concept of the imagined extremist community elucidates how lone actors, especially those embracing right-wing ideologies, are subject to radical influences. Their conservative traits and psychological dispositions make them particularly receptive to the appeal of such communities.